Properly aligned band structures in B-TiO2/MIL53(Fe)/g-C3N4 ternary nanocomposite can drastically improve its photocatalytic activity for H2 evolution: Investigations based on the experimental results. (18th June 2021) - Pi, Wenbo; Humayun, Muhammad; Li, Yuan; Yuan, Yang; Cao, Junhao; Ali, Sher; Wang, Mei; Li, Honglang; Khan, Abbas; Zheng, Zhiping; Fu, Qiuyun; Tian, Yahui; et al.
Abstract: The development of new tools that could meet the demand of sustainable energy production has attracted worldwide scientific attention. Over the past few decades, significant research efforts have been carried out to efficiently reduce water to H2 (green fuel) over semiconductor photocatalysts. Numerous semiconductor photocatalysts have been employed in photocatalysis for optimum H2 production. All the techniques were chosen based on their flexibility, cost-effectiveness, and ease of availability. Recently, polymeric carbon nitride (g-C3 N4 ) received worldwide attention in visible light photocatalysis for energy and environmental applications due to its low price, robust nature, and superior thermal stability. Nevertheless, g-C3 N4 (CN) exhibits shortfalls such as high charge carrier's recombination rate and weak reduction ability. To overcome these drawbacks, herein, for the first time we have fabricated B-TiO2 /MIL-53(Fe)/CN ternary composite via hydrothermal and wet-chemical methods. The resultant B-TiO2 /MIL53(Fe)/CN ternary composite shows drastically improved photocatalytic activity for hydrogen evolution compared to the bare CN, B-TiO2, and MIL53(Fe) components. The B-TiO2 /MIL53(Fe)/CN ternary composite produced approximately 166.3 and 581.2 μmol h −1  g −1 of hydrogen under visible light and UV–visible light irradiations, respectively, with the assistance of co-catalyst Pt. Photo-luminescence (PL) and the fluorescence (FL) spectroscopy measurements reveal that the enhanced photoactivity is due to the greatly promoted charge carrier's separation and transfer at the interfacial contact of the well-aligned three-component systems. This work will promote the design and development of efficient photocatalyst based on CN for clean energy production and environmental purification. Graphical abstract: Image 1 Highlights: B-TiO2 /MIL-53(Fe)/g-C3 N4 ternary composite has successfully been fabricated. The ternary composite exhibited improved photoactivity for H2 evolution. Charge separation drastically improved due to the well aligned three components. A clear photocatalytic mechanism is proposed based on the experimental results.